2019
DOI: 10.14814/phy2.14225
|View full text |Cite
|
Sign up to set email alerts
|

Abaloparatide exhibits greater osteoanabolic response and higher cAMP stimulation andβ‐arrestin recruitment than teriparatide

Abstract: Teriparatide and abaloparatide are parathyroid hormone receptor 1 (PTHR1) analogs with unexplained differential efficacy for the treatment of osteoporosis. Therefore, we compared the effects of abaloparatide and teriparatide on bone structure, turnover, and levels of receptor activator of nuclear factor‐kappa B ligand (RANKL) and osteoprotegerin (OPG). Wild‐type (WT) female mice were injected daily with vehicle or 20–80 µg/kg/day of teriparatide or abaloparatide for 30 days. Femurs and spines were examined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 118 publications
5
26
3
1
Order By: Relevance
“…Another recent report from Sahbani et al. also showed similar effect of ABL and PTH at doses comparable to those used in the present investigation ( 43 ). In contrast to these pre-clinical findings, clinical studies have reported greater aBMD response rates in osteoporotic patients treated with ABL compared with patients treated with PTH ( 23 , 54 ).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Another recent report from Sahbani et al. also showed similar effect of ABL and PTH at doses comparable to those used in the present investigation ( 43 ). In contrast to these pre-clinical findings, clinical studies have reported greater aBMD response rates in osteoporotic patients treated with ABL compared with patients treated with PTH ( 23 , 54 ).…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with the present study, which found that PTH and ABL lead to similar amounts of osteoclast covered surfaces at the proximal tibial metaphysis. This finding is further corroborated by a very recent study, which showed that the same dose of PTH and ABL resulted in similar serum CTX values in intact female mice ( 43 ). Therefore, despite the overall anabolic effect of PTH and ABL, the elevated bone turnover increases the likelihood of perforating trabeculae.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Recently, abaloparatide, a parathyroid hormone-related protein (PTHrP), was approved by Food and Drug Administration (FDA) for the treatment of severe post-menopausal osteoporosis (26). A recent study performed by Sahbani et al compared abaloparatide to teriparatide on bone structure, turnover, and levels of RANKL and OPG on wild-type female mice (27). The authors showed that 20-80 µg/kg/day of abaloparatide for 30 days resulted in a significant increase (13%) in trabecular bone thickness and lowered the RANKL/OPG ratio.…”
Section: Parathyroid Hormonementioning
confidence: 99%